HO CHI MINH’S MULTICULTURAL THOUGHTS - Jingqing, Yang (UI Scholars Hub, 2019)
Ho Chi Minh is one of influential personages in the history of Vietnam. His thoughts became the crucial guideline in the anti-colonial, anti-imperialist and independence movements of Vietnam. So far, quite a few scholars have conducted in-depth analysis of Ho Chi Minh‟s thoughts from the perspectives of politics, sociology and philosophy, but few scholars have studied Ho‟s thoughts from the perspective of multiculturalism. Given that multiculturalism is a theory that firstly put forward by western scholars in the western world, whether the theory is applicable to traditional and communitarian oriental world has become a hot topic in academic circles. From the perspective of morality, the elements of liberty, equality and justice of multiculturalism have the function of anti-colonialism and anti-imperialism in Southeast Asian countries including Vietnam. In the colonial times, French deliberately isolated Vietnamese ethnic groups through ideological control and geographical isolation, but under the guideline of Ho Chi Minh‟s thought, the Vietnamese broken the barrier of colonial and successfully achieve national unity and ethnic unity. This paper intends to prove that multiculturalism has the function of anti-colonialism and anti-imperialism by researching the Ho Chi Minh‟s multicultural thoughts, which is the best practice of western multiculturalism in southeast Asia.